The Group of Units of Integral Group Rings of Extra-Special 2-Groups (European Journal of Pure and Applied Mathematics, 2017)
One of the main problems on group rings is to determine its group of units. In this paper, we describe the group of units of integral group rings of two extra-special 2-groups: one of order 32, Â the central product of two copies of D_4, and another of order 128, the central product of three copies of D_4.